Effects of pcv2 vaccine on the growth performance of pigs and mortality rate in a pcv2-positive commercial swine herd - J Y Jacela; R C Sulabo; J R Bergstrom; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2007)
A total of 1,470 pigs were used to study a commercial sow herd with a history of Porcine Circovirus Disease (PCVD). The objective was to evaluate the effect of two commercially available Porcine Circovirus Type 2 (PCV2) vaccines on growth and mortality rates. The first vaccine was administered one week after weaning (1-dose) while the second was administered at weaning and repeated three weeks later (2-dose). A third group of unvaccinated pigs served as a control group. Pigs were individually weighed at weaning (d 0), d 113, 143, and just prior to market. On d 113, pigs on the 2-dose treatment were heavier (P<0.05) than the control group, and the 1-dose treatment pigs were intermediate. At d 143, just prior to when the first pigs were marketed, both the 1-dose and the 2-dose pigs were heavier than the control pigs by 7.6 and 10.2 lb (P<0.05), respectively, and there were no significant differences in weights between the two vaccinated groups. However, differences in weights between the vaccinated and the control pigs were smaller at off-test compared to differences at d 143 due to a wider variability in on-test days as a result of multiple marketing days prior to end of the trial. Although there were no significant differences between the two vaccinated groups, ADG was greater (P<0.05) in all vaccinated pigs compared to non-vaccinated control pigs from d 0 to d 113, d 143, and at off-test. From d 113 to 143 and until the day they were taken off test, there were no differences in ADG, regardless of treatment. This suggests that the increase in growth rate in vaccinated pigs occurred during the period d 0 to 113. Barrows consistently exhibited greater ADG and heavier weights (P<0.05) than gilts throughout the trial. No significant differences in mortality rate between treatments were observed but both vaccinated groups had mortality rates that were 3% lower than the non-vaccinated control pigs. Based on these results, both commercial vaccines were effective in mitigating the effects of PCV2 virus and improving the growth performance of pigs in a PCV2 positive herd.; Swine Day, 2007, Kansas State University, Manhattan, KS, 2007
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-121-S; Swine day; 2007; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 985; Swine; Health; PCVAD; PCV2